The exposure and perception of Cebuanos on the Tagalog Language their implications to the bilingual education policy of the Philippines - Aday, Ma. Dolores L. (Danyag :the UPV journal of humanities and social sciences, 2006)
"This paper presents the findings of a research conducted on the exposure and perception of Cebuanos to the Tagalog language through soap operas. The findings are related to parallel concepts found in other literature exploring the links between mass media exposure and perception of a language other than one's own tongue. The possible implications on the bilingual education policy of the Philippines are also explored. The Cebuanos were found to have substantial exposure to the Tagalog language and they hold a positive perception and a neutral attitude toward the language. Given Cebuano's exposure to the Tagalog language through the communications media, the school is no longer an essential venue for the effective spreading of Tagalog. It is suggested that schools therefore should focus more on improving English language competency so that students will be globally competitive."